Hybrid imidazo[1, 2‐a]pyridine analogs as potent ATX inhibitors with concrete in vivo antifibrosis effect. Issue 10 (3rd June 2022) - Li, Tong; Lei, Hongrui; Yang, Juanjuan; Cao, Zhi; Yang, Yu; Liu, Zimeng; Sun, Ruonan; Yang, Xinlian; Zhai, Xin
Abstract: In recent years, small‐molecule inhibitors targeting the autotaxin (ATX)/lysophosphatidic acid axis gradually brought excellent disease management benefits. Herein, a series of imidazo[1, 2‐ a ]pyridine compounds (1 –11 ) were designed as ATX inhibitors through a hybrid strategy by combining the imidazo[1, 2‐ a ]pyridine skeleton in GLPG1690 and the benzyl carbamate moiety in PF‐8380. As indicated by FS‐3‐based enzymatic assay, the carbamate derivatives revealed moderate to satisfying ATX inhibitory potency (IC50  = 23–343 nM). Subsequently, the carbamate linker was altered to a urea moiety (12 –19 ) with the aim of retaining ATX inhibition and improving the druglikeness profile. The binding mode analysis all over the modification process well rationalized the leading activity of urea derivatives in an enzymatic assay. Following further structural optimization, the diethanolamine derivative 19 exerted an amazing inhibitory activity (IC50  = 3.98 nM) similar to the positive control GLPG1690 (IC50  = 3.72 nM) and PF‐8380 (IC50  = 4.23 nM). Accordingly, 19 was tested directly for in vivo antifibrotic effects through a bleomycin model (H&E staining), in which 19 effectively alleviated lung structural damage and fibrosis at an oral dose of 20 and 60 mg/kg. Collectively, 19  qualified as a promising ATX inhibitor for potential application in fibrosis‐relevant disease treatment. Abstract : A hybrid strategy by combining the imidazo[1, 2‐a]pyridine skeleton in GLPG1690 and the benzyl carbamate moiety in PF‐8380 identified compound 19 (IC50  = 3.98 nM) as the optimal autotaxin inhibitor. Further biological evaluation confirmed that compound 19 is a potential candidate for the regulation of fibrosis‐relevant diseases.